Peningkatan Pemahaman Sumber Daya Manusia dan Implementasi Regulasi dalam Pusat Pembelajaran Keluarga (PUSPAGA) Kota Baubau - La Ode Dedi Abdullah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
Increased understanding of human resources about the regulation of family learning centers (PUSPAGA) in Baubau City is very necessary, this is because it can support and grow / increase understanding of human resources on the importance of family learning centers so that a city with quality families can be realized. This activity is motivated by the problem that there are still many people who are not fully aware of the existence of a family learning center, how to participate in the membership of a family learning center and the number of people who do not fully know and implement the values/legal rules that contain prohibitions and orders for do not commit Domestic Violence. This activity aims to increase understanding of: 1) knowledge of human resources, 2) how to get family learning center services and 3) understanding and implementing legal values/rules that contain prohibitions and orders not to commit domestic violence. . The method of this service activity is socialization, counseling, and discussion. This activity was carried out in 2020 with participants being people who have received PUSPAGA services in Baubau City. The result of this activity is an increase in public understanding about the importance of human resources, the community knows how to get services at PUSPAGA and the implementation of regulations in a good family learning center will certainly encourage the growth of a harmonious family.